2015
DOI: 10.4172/2167-0420.1000271
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Sensitivity, Biochemical Characteristics and Biotyping of Staphylococcus saprophyticus: An Impact of Biofield Energy Treatment

Abstract: Staphylococcus saprophyticus (S. saprophyticus) is a Gram-positive, coagulase-negative facultative bacterium belongs to Micrococcaceae family. It is a unique uropathogen associated with uncomplicated urinary tract infections (UTIs), especially cystitis in young women. Young women are very susceptible to colonize this organism in the urinary tracts and it is spread through sexual intercourse. S. saprophyticus is the second most common pathogen after Escherichia coli causing 10-20% of all UTIs in sexually active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 30 publications
(18 reference statements)
1
58
0
Order By: Relevance
“…Biofield Energy Healing Treatment (The Trivedi Effect ® ) has been published in numerous peerreviewed science journals due to its significant impacts in the science fields of biotechnology, genetics, cancer, microbiology, materials science, agriculture, and pharmaceuticals. These publications reported that Biofield Energy Treatment (The Trivedi Effect ® ) has the astounding capability to transform the physical, structural, chemical, thermal and behavioral properties of several pharmaceuticals [23][24][25], nutraceuticals [26,27], organic compounds [28][29][30], metals and ceramics in materials science [31][32][33], improve the overall productivity of crops [34][35][36], as well as modulate the efficacy of various living cells [37][38][39][40]. Although magnesium gluconate exhibits the highest bioavailability and moderate solubility in water in comparison to other magnesium salts, humans still face problems in achieving their daily requirements of magnesium [41].…”
Section: Introductionmentioning
confidence: 99%
“…Biofield Energy Healing Treatment (The Trivedi Effect ® ) has been published in numerous peerreviewed science journals due to its significant impacts in the science fields of biotechnology, genetics, cancer, microbiology, materials science, agriculture, and pharmaceuticals. These publications reported that Biofield Energy Treatment (The Trivedi Effect ® ) has the astounding capability to transform the physical, structural, chemical, thermal and behavioral properties of several pharmaceuticals [23][24][25], nutraceuticals [26,27], organic compounds [28][29][30], metals and ceramics in materials science [31][32][33], improve the overall productivity of crops [34][35][36], as well as modulate the efficacy of various living cells [37][38][39][40]. Although magnesium gluconate exhibits the highest bioavailability and moderate solubility in water in comparison to other magnesium salts, humans still face problems in achieving their daily requirements of magnesium [41].…”
Section: Introductionmentioning
confidence: 99%
“…The Biofield Energy Healing Treatment (The Trivedi Effect ® ) has been published in numerous peerreviewed science journals due to its significant impacts in the science fields of biotechnology, genetics, cancer, microbiology, materials science, agriculture, and pharmaceuticals. These publications reported that the Biofield Energy Treatment (The Trivedi Effect ® ) has the astounding capability to transform the physical, structural, chemical, thermal and behavioral properties of several pharmaceuticals [23][24][25], nutraceuticals [26,27], organic compounds [28][29][30], metals and ceramic in materials science [31][32][33], and improve the overall productivity of crops [34][35][36] as well as to modulate the efficacy of the various living cells [37][38][39][40]. Although magnesium gluconate exhibits the highest bioavailability and moderate solubility in water in comparison to other magnesium salts, humans still face problems in achieving their daily requirements of magnesium [41].…”
Section: Introductionmentioning
confidence: 99%
“…[10,11]. Biofield Energy Healing Treatment (The Trivedi Effect ® ) is drawing importance in several fields include material science [12], pharmaceuticals [13], nutraceuticals [14], organic compounds [15,16], microbiology [17], agricultural [18], biotechnology [19], genetics [20], medical [21] due to its amazing ability for modification of the characteristic properties of the numerous non-living and living substances. Scientific literature extensively reported significant problems about the bioavailability of vitamin B6.…”
Section: Introductionmentioning
confidence: 99%